Legal Measures to Ensure the Safety of Loading and Unloading Workers at PT. Belawan Indah (TKBM) - Dina Rizka Yusra; Darma, Mospa; Sitepu, Karolina; Elyani, Elyani (Universitas Pahlawan Tuanku Tambusai, 2024)
Law Number 13 of 2003 concerning Manpower and Joint Decree of the Director General of Manpower Supervision Development, Director General of Sea Transportation, and Deputy Institutional Cooperatives and Small and Medium Enterprises Number: UM.008/41/2/DJPL-11, Number: 93/DJPPK/XII/20111, and Number: 96/SKB/DEP.1/XII/2011 concerning Employment Protection is the government's mandate to protect workers' rights. Workers who load and unload goods to and from ships at the port are known as Loading and Unloading Workers (TKBM) and are a vital component of port human resources. Due to its more specialized role in loading and unloading machinery, TKBM is an important component of human resources which is very important for all activities in the port. Primary and secondary data from relevant literature and laws and regulations are used in this study, which are descriptive analysis and use empirical legal methods in the research. Based on the findings of the research, workers at PT. Belawan Belawan Indah Port is legally protected when loading and unloading cargo, such as protection of wages, working hours, occupational safety, and welfare, and factors that hinder legal protection, such as ships, weather, ports, equipment, are still not properly implemented.